Percepción de la violencia de género en comunidades Shuar de la provincia de Zamora Chinchipe - Díaz, Martha G. (2020)
Gender violence is a social problem, however, no studies have been developed in the case of the indigenous communities (Shuar), nor in other areas further away from the city, for this reason it is necessary to study them. The Shuar indigenous community in Ecuador is the object of this investigation, given that the forensic psychological evaluations carried out in the cities where these communities exist, show that despite the gender violence that exists, Shuar women have naturalized the aggressive behavior they receive from the male population of their community. Causes and consequences of the problem of gender violence in the Shuar community are scientifically unknown, the few studies that have been carried out on these peoples have been developed from a anthropological and demographic. Due to the aforementioned, the present study intends to make a analysis in which the causes and consequences of gender-based violence in the Shuar indigenous community and the perception of Shuar women.